Regenerated Shoot Number and Coppicing Ability of Two Year Old Eucalyptus tereticornis Stumps of Different Girth Classes - Babitha, M.; Sreenivasulu, A.; Meru, Elusing; Rao, P. S. (Indian Forester, 2000)
Stumps of different girth classes of Bhadrachalam clone-l of Eucalyptus tereticornis of the same age were selected and coppiced. The coppice shoots were collected four times, each at 15 days interval separately from each of the girth classes and counted. It was observed that with the increase in the girth of the coppiced stump, the number of shoots produced per stump increased significantly. However no significantly differences were observed between the harvests. Thus it can be concluded from this study that the ability to produce coppice shoots may, in some way be related to the size of the donor tree, which may be due to increased coppicing ability or due to greater carbohydrate reserves in stumps of greater girth.